Essays on the political economy of trade liberalisation - Soegaard, Christian (2012)
This doctoral thesis contributes to a growing strand of literature on the nature and causes of trade liberalisation from a political economy perspective. In three core chapters, I identify distinct and novel features of trade liberalisation. In Chapter 2, I demonstrate that unilateral and cooperative trade policy depend crucially on the degree of natural trade costs, or transport costs, in a model where terms-of-trade and profit-shifting motives for trade policy are important. When trade costs decline, a conflict of interest between unilateral and cooperative trade policy intensifies: unilateral policy aims to optimally exploit a country's monopoly power over its terms of trade, whereas cooperative policy aims to minimise losses in transit. In a framework where cooperative trade policy must be sustained by a reputational mechanism, I demonstrate that import tariffs can be lowered in response to decreases in natural trade costs, provided the long-run cooperative objectives of minimising losses in transit are more important than the short-run temptation of distorting the terms of trade and shifting profits towards the domestic market. These temptations become larger when trade costs decline since when the degree of natural distortions of consumer prices, and the degree of natural profit-shifting are lower, import tariffs are more effective at doing the job. I also demonstrate that a free trade agreement can be supported for a larger range of discount factors when trade costs decline. In Chapter 3, I analyse the sustainability of unilateral and bilateral trade liberalisation by introducing a time-inconsistency problem in addition to standard terms-of-trade manipulations. I find that the government's bargaining power vis-a-vis a politically organised lobby is a key parameter in the determination of the sustainability of trade liberalisation. Unilateral trade liberalisation, which is when the government unilaterally sets the dynamically efficient trade policy, can be sustained for every discount factor if the government has no bargaining power. This is because when the government has no bargaining power, it is only just compensated for the short-run distortion associated with trade policy, and not for the long-run distortions which come about from overinvestment in protected sectors. As the government's bargaining power increases, the level of patience required to sustain unilateral trade liberalisation also increases, and when the bargaining power exceeds a critical threshold, the government is able to extract so much rent that it is better off continuing its implicit contract with the lobby. Bilateral trade liberalisation imposes further sanctions on the part of a deviating country when its trading partner punishes it. This ensures that bilateral trade liberalisation can be sustained for all levels of the government's bargaining power provided the world is sufficiently patient. However, for low bargaining powers unilateral trade liberalisation can be supported for a larger range of discount factors whereas when the bargaining power exceeds a critical level, a trade agreement is needed to sustain trade liberalisation. In the last of the core chapters, Chapter 4, the question I address is one of the nature rather than the causes of trade liberalisation as in the two chapters that preceded it. I carry out an empirical examination of the political-economy model in Maggi and Rodriguez-Clare (2007). The model makes clear predictions regarding the tariff cuts in a trade agreement which can be perfectly enforced internationally. There are two distortions of non-cooperative trade policy: terms-of-trade manipulations, and a dynamic inconsistency. Thus, when two countries come together to sign a trade agreement these are the distortions they solve. The model predicts that tariff cuts should be explained by a terms-of-trade component, which I capture by the value of net imports, and inter-industry capital mobility, which I measure using three different variables: persistence of profits, capital-labour ratios and four-firm concentration ratios. I find that the first two variables capturing capital mobility perform very well at explaining the speed of liberalisation of US import protection on Mexican products. The results on the terms-of-trade component are less convincing although on most econometric specifications I obtain the correct sign.